KARAKTERISTIK FONOLOGIS LEKSIKON DIALEK BAHASA JAWA BREBES PERBATASAN DENGAN BAHASA JAWA STANDAR: KAJIAN DIALEKTOLOGI KONTEMPORER - Rizal, Ghulam Arif (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the phonological characteristics of the lexicon of the Brebes Javanese dialect used in the Sunda border region, with Standard Javanese (Jogja-Solo). The purpose of the study was to identify the phonological differences in variation that emerge from the standard language and to analyze the factors that influence these variations. The research method used was descriptive qualitative with data collection techniques through in-depth interviews with informants who met certain criteria. The results of the study showed that the Brebes Javanese dialect has several different phonological characteristics compared to standard Javanese, occurring in the more open vowel [a], neutralization of vowels [i] and [u], and reduction of retroflex consonants [ʈ] and [ɖ] to [t] and [d]. In addition, a syllable stress pattern was also found compared to Standard Javanese. Factors such as geographical isolation, the influence of neighboring languages ​​(Banyumas and Sundanese), and natural phonological changes also contribute to these differences. These findings provide an important contribution to the understanding of dialect diversity in Javanese and efforts to preserve regional languages ​​in Indonesia. This study also recommends the need for further study of the impact of globalization on phonological changes in Javanese dialect.